1998
DOI: 10.1093/ajcp/110.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor-Associated Gastric Polyps: A Retrospective Analysis of Their Frequency, and Endoscopic, Histologic, and Ultrastructural Characteristics

Abstract: A b s t r a c tProton pump inhibitors (PPIs) are a benzimidazole-substituted class of antisecretory agents. They have been available for general use in the United States since 1989. These small molecules decrease parietal cell acid secretion by inhibiting hydrogen/potassium-exchanging adenosine triphosphatase. This enzyme catalyzes the final step in the secretion of acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
1
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 5 publications
5
107
1
5
Order By: Relevance
“…In contrast to reports by Carmack et al (10) and Stolte et al (30), in which fundic gland polyps were reported as the most common gastric polyps, with a relative frequency of 77% and 47%, respectively, in our study, fundic gland polyps accounted for less than 6.1% of all polyps. Fundic gland polyps have almost no malignant potential when they are associated with the use of PPIs (11,31,32) or when they occur sporadically (33). Similarly, we found neither dysplasia nor malignancy in the fundic gland polyps in our study.…”
Section: Discussionsupporting
confidence: 44%
“…In contrast to reports by Carmack et al (10) and Stolte et al (30), in which fundic gland polyps were reported as the most common gastric polyps, with a relative frequency of 77% and 47%, respectively, in our study, fundic gland polyps accounted for less than 6.1% of all polyps. Fundic gland polyps have almost no malignant potential when they are associated with the use of PPIs (11,31,32) or when they occur sporadically (33). Similarly, we found neither dysplasia nor malignancy in the fundic gland polyps in our study.…”
Section: Discussionsupporting
confidence: 44%
“…Chronic ECL cell stimulation also results as reflected by increased levels of chromogranin A, an endocrine cell product [22] . In recent years, gastric fundic gland polyps have become increasingly detected in patients on long-term proton pump inhibitor therapy [23][24][25][26] . These fundic gland polyps are often multiple in this setting and localized in the gastric body and fundus.…”
Section: Proton Pump Inhibitor-associated Gastric Polypsmentioning
confidence: 99%
“…PPIs are also used adjuvantly in the eradication of H. pylori 3) . With widespread use of PPIs came reports of gastric mucosal changes including fundic gland hyperplasia 4) , cystic dilation of fundic glands (oxyntic dilatation) 5) 6) , emergence and enlargement of socalled fundic gland polyps (FGPs) [7][8][9][10][11] , and morphologic changes in parietal cells 12) . The parietal cell protrusions (PCPs) found in patients treated with omeprazole are thought to be an especially characteristic change [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%